Tratamiento Tributario Aplicable a las Entidades Sin Ánimo de Lucro (ESAL) - Caso de Estudio Corporación Banco de Tejidos Regional Sur, cuya sigla es “bantejido” (2022)
This degree work has been developed with the intention of making a contribution that is useful for; students, Public Accounting professionals and related careers, and of course for the directors and/or managers of non-profit entities -ESAL- on the tax aspects of this type of associative forms. In the long run, it will become a guide document to resolve doubts that arise about formal obligations, the determination of net profit or surplus, and the calculation of income tax. From the perspective of the authors, this degree project makes an important contribution to the academy and the profession, since it resolves the constant doubts about the tax treatment of this type of entity. Since it describes, analyzes and resolves this type of very frequent concerns in the first months of the year, when tax maturities begin in Colombia.